The Impact of Foreign Bank Deleveraging on Korea - Jain-Chandra, Sonali (IMF Working Papers; Working Paper ;, 2013)
Korea was hit hard by the 2008 global financial crisis, with the foreign bank deleveraging channel coming prominently into play. The global financial crisis demonstrated that a sharp deleveraging can be transmitted to emerging markets through the bank lending channel to a slowdown in credit growth. The analysis finds that a sharp decline in external funding led to relatively modest decline in domestic credit by Korean banks, due to concerted policy efforts by the government in 2008. Impulse responses from a Dynamic Stochastic General Equilibrium (DSGE) model calibrated to Korea shows that it appears better prepared to handle such shocks relative to 2008. Indeed, Korea is much more resilient to such shocks due to the efforts by the authorities, which has led to the strengthening of external buffers, such as higher foreign exchange reserves and bilateral and multilateral currency swap arrangements.